Implementation of Multi-Attribute Utility Theory (MAUT) Method in Gaming Laptop Selection - S, Wahyu Ardiantito; Ramadhani, Suci; Jesika, Stacyana (Jurnal Bumigora Information Technology (BITe), 2024)
Background: This time, laptops are an essential piece of technology because these instruments can be used for various tasks, including work, play, and education.Objective: This research aims to develop a decision support system using the MAUT method for selecting gaming laptops.Methods: The method used in this research is MAUT which is applied to the selection of gaming laptops.Result: Based on calculations that have been carried out using the MAUT method, it is found that the MSI Cyborg Katana laptop (B13VGK) is the first ranked gaming laptop with a utility value of 0.7035.Conclusion: The implementation of MAUT for gaming laptop selection is proven to be applicable.